Copper Poisoning with Emphasis on Its Clinical Manifestations and Treatment of Intoxication - Mehrdad Rafati Rahimzadeh; Mehravar Rafati Rahimzadeh; Sohrab Kazemi; Ali Akbar Moghadamnia (Advances in Public Health)
Background. Copper is an essential trace element found in the human body in an oxidized (Cu II) and reduced (Cu I) form. It plays a crucial role in the integrity and function of proteins and enzymes. Short-term and long-term exposure to copper can result in harmful effects and lead to clinical manifestations in multiple bodily systems, including the gastrointestinal tract, liver, kidneys, eyes, respiratory, cardiovascular, central nervous, endocrine, and hematopoietic systems. Objective. The purpose of this study is the importance of early recognition and diagnosis of copper poisoning immediate and necessary measures and the use of chelators. Materials and Methods. In this review article, authors from Pub Med, Scopus, and a toxicologic emergencies reference book from 1996 to 2024 are used. Result. An excessive increase in copper level produces reactive oxygen species that can cause lipid peroxidation in cell membranes, direct oxidation of proteins, and the breakdown of DNA and RNA molecules. All of these can generally be reasons for cell death. Conclusion. Assessing levels of copper in whole blood, free serum copper, 24-hr urine copper, liver biopsy for copper concentration, and ceruloplasmin play a crucial role in the diagnosis. The blood copper concentration is directly related to the severity of poisoning. Treatment for copper poisoning typically involves removing the source of exposure and administering medications to help remove the excess copper from the body. Supportive care for copper intoxication usually includes managing vomiting, correcting fluids and electrolytes, and stabilizing vital signs. Chelators like D-penicillamine, succimer, trientine, tetrathiomolybdate, and PBT-2 have been utilized in treatment.